Peran Komunikasi Pembangunan dalam Mewujudkan Mesjid Mandiri (Al-Muslimin) di Kota Medan - Joni Romaito Ritonga; Fachri Chairozi; Siti Fadilah; Cindi Indarti Kesuma; Irma Yusriani Simamora (Universitas Muhammadiyah Enrekang, 2022)
Until now, Indonesia is still one of the developing countries, where most of the population lives in rural areas and around 50% of the population lives from agriculture. Therefore, the development communication strategy is still focused on rural areas. This is in accordance with the opinion of Depari and Mc Andrews (1991) that until now the development communication strategy is still limited to rural broadcasts, both through mass media and the use of development extension officers. Therefore, it is necessary to think further, how existing communication efforts can be developed, especially in facing the challenges of the globalization era.